The effects of perceived ease of use, electronic word of mouth and content marketing on purchase decision - Asnawati Asnawati (Growing Science, 2022)
Purchasing decisions on the Traveloka application has experienced a significant decline since the Covid-19 pandemic outbreak. Ticket returns and refunds that occur due to travel restrictions have resulted in a decline in Traveloka's brand image. This study aims to analyze how brand image mediates the effect of perceived ease of use, electronic word of mouth and content marketing towards ticket purchasing decisions on the Traveloka application which was conducted on 130 respondents using the Traveloka application. The research was conducted in June 2021 with data analysis using SmartPLS 3.2.0 software. The results show that perceived ease of use had a negative impact on purchasing decisions, either directly or indirectly through brand image. Electronic word of mouth had a positive impact on purchasing decisions either directly or indirectly through brand image. Content marketing had a negative and significant impact on purchasing decisions, while indirectly through brand image had a positive and significant impact. The role of brand image was very important in increasing the effect of perceived ease of use, electronic word of mouth and content marketing towards purchasing decisions.